Síntese e avaliação fotofísica de compostos fulereno[60]-glicoconjugados - Silva, Rafael Santos da (2018)
In the midst of a variety of alternative therapies in the treatment of several diseases, the photodynamic therapy appears as a versatile protocol. This therapy uses the absorptive properties of photoactive molecules, called photosensitizers and light itself, for the treatment some diseases caused by viruses, bacteria and even some type of tumors. The aim of this work is the synthesis of fullerene [60] -glycolonjugates compounds and the evaluation of their photophysical properties for the use as potential photosensitizers in photodynamic therapy. In this context, the synthesis of 10 C60 Fulerene derived compounds, conjugated to different carbohydrate residues, linked through 1,2,3-triazoyl-malonate moieties were obtained through two different types of cycloaddition reactions. The bis (1- (glycosyl) -5H-1,2,3-triazol-4-alkynyl) malonates (3aa-3ae and 3ba-3be) were obtained through a CuAAc 1,3-dipolar cycloaddition between the acetylenic malonates (2a, 2b) and glycosyl azides (1a-1e). The incorporation of bis (1- (glycosyl) -5H-1,2,3-triazol-4-alkynyl) malonates was carried out through a Bingel-Hirsch type cycloaddition with C60 fullerene, using iodine (I2), DBU as base, in monochlorobenzene for 4 h at room temperature, leading to fullerene[60]-glycolonjugates (4aa-4a and 4ba-4b). The singlet oxygen generation capacity of fulerene[60]-glycolonjugates compounds was evaluated by DPBF photodegradation assays. Then the quantum yields of singlet oxygen generation were quantified for the compounds. The results were considered satisfactory when compared to the pure C60 fulerene used as standard. So, these results accredit the fulerene[60]-glycolonjugates synthesized as potential photosensitizers, for the use in photodynamic therapy.